MEMBANGUN KOMUNIKASI INTERPERSONAL MAHASISWA RANTAU TELKOM UNIVERSITY DALAM UPAYA MENGATASI KESEPIAN TANPA PASANGAN - siska Amelia amelia (Program Studi Ilmu Komunikasi FISIP UM Buton, 2021)
As a student, living in pairs is desirable, especially for overseas students. Because they are social creatures who always socialize with other people, they are also very vulnerable to the risk of loneliness and other psychological problems when there is no sense of belonging in themselves. Of course this research wants to understand about Building Interpersonal Communication of Telkom University Overseas Students in an effort to overcome loneliness without a partner. This research is a qualitative research with a constructivist paradigm and a phenomenological approach. Research informants are Telkom University overseas students who experience depression and loneliness without a partner. Data collection techniques with interviews as the main method and observation as a supporting method. The results show that overall, it shows that the interpersonal communication process based on relational maintenance starts from introductions, intimate relationships, conflicts, to termination, and in building relationships that occur in overseas students of Telkom University, we can conclude that it turns out that building good relationships with partners is very important, so that relationships stay awake, and avoid loneliness without a partner. But even so, relationships never always run smoothly so that it can lead to separation even though the relationship that has been established has gone through the stages of overcoming the breakup. If this happens to overseas students, students will try to open up by socializing with the people around them so that they no longer experience loneliness without a partner. Keywords: Lonely, Interpersonal Communication, Overseas Students Telkom University, Relational Maintenance